Pedagogical reflective practice of nursing undergraduates: the portfolio as an instrument - Vaz, Débora Rodrigues; Prado, Cláudia (Revista da Escola de Enfermagem da USP, 2014)
Objective Analyzing the narratives related to the pedagogical practice experienced during the Supervised Curricular Internship reported in the portfolios of Nursing undergraduate students, regarding the levels of reflection. Method This is a documentary descriptive exploratory study that examined two of the activities proposed for the portfolio preparation. Results Among the 28 analyzed portfolios, all showed the three levels of reflection (technical, critical and metacritical). Conclusion The students had the opportunity to experience the pedagogical practice and presented reflections at metacritical level, reflecting on their performance, the construction of their teaching identity, and about the importance of reflecting on the practice with the objective of transforming it and transforming themselves.